Synthesis, Crystal Structure, and DFT Study of Two New Dinuclear Copper(I) Complexes Bearing Ar‐BIAN Ligands Functionalized with NO2 Groups. Issue 30 (13th July 2020) - Outis, Mani; Rosa, Vitor; Laia, César A. T.; Lima, João Carlos; Barroso, Sónia; Carvalho, Ana Luísa; Calhorda, Maria José; Avilés, Teresa
Abstract : Two new bis(aryl‐imino)‐acenaphthene, Ar‐BIAN (Ar = 2, 4, 6‐trimethylphenyl = mes) ligands, bearing the NO2 group in the naphthalene moiety of the iminoacenaphthene at para‐ (5‐NO2 ) and meta‐ (4‐NO2 ) position, of formulations 1, 2‐bis(mes‐imino)‐5‐nitroacenaphthene, 1, and 1, 2‐bis(mes‐imino)‐4‐nitroacenaphthene, 2, were synthesized. Their respective dinuclear iodide bridged copper(I) complexes [Cu2 (µ‐I)2 (mes‐BIAN‐5‐NO2 )2 ], 3 and [Cu2 (µ‐I)2 (mes‐BIAN‐4‐NO2 )2 ], 4, were obtained in good yields by treatment with an equimolar amount of CuI. All compounds were characterized by elemental analysis, single‐crystal X‐ray diffraction, 1 H‐NMR, 13 C‐NMR, FTIR, UV/Vis spectroscopy. DFT calculations helped to understand the different molecular structure observed in the crystals of 3 and 4 and the determining role of packing forces. TDDFT revealed that the absorption bands in the visible were essentially MLCT (Metal to Ligand Charge Transfer), with some n→π* character (intra ligand). The shift to the red compared to the spectrum of the Cu(I) complex analogue without the NO2 group, [Cu2 (µ‐I)2 ](mes‐BIAN)2 ], 6, could be explained by the stabilization of the ligand unoccupied π* orbitals in the presence of NO2 . Abstract : Cu(I) complexes [Cu2 (µ‐I)2 (LL)2 ] bearing two new bis(aryl‐imino)‐acenaphthene (LL) ligands, each with one NO2 group in the naphthalene moiety were synthesized. The different arrangements of the {Cu2 (µ‐I)2 } cores, one planar and the other puckered, were assigned to packing forces, based on the X‐ray structures and DFT calculations. Absorption bands in the visible were essentially MLCT.